2022
DOI: 10.1016/j.xkme.2021.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Socioeconomic Disparities in CKD in the Context of Universal Health Care Provided by the Military Health System

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Norton et al (2021) investigated disparities in CKD within the context of the military healthcare system. The results of their cross-sectional study suggest that there is an increased incidence of CKD in older enlisted service members as compared to senior officers [ 33 ]. Because the military provides all its members with adequate insurance coverage through the TRICARE Health Plan, this disparity is unlikely to be caused by differences in insurance coverage.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Norton et al (2021) investigated disparities in CKD within the context of the military healthcare system. The results of their cross-sectional study suggest that there is an increased incidence of CKD in older enlisted service members as compared to senior officers [ 33 ]. Because the military provides all its members with adequate insurance coverage through the TRICARE Health Plan, this disparity is unlikely to be caused by differences in insurance coverage.…”
Section: Reviewmentioning
confidence: 99%
“…Because the military provides all its members with adequate insurance coverage through the TRICARE Health Plan, this disparity is unlikely to be caused by differences in insurance coverage. The authors conclude that the findings of their study may be attributable to social and cultural factors [ 33 ].…”
Section: Reviewmentioning
confidence: 99%
“…Social determinants of health that have been associated with depression and anxiety in CKD include sex, race or ethnicity, education, employment, marital status, and specific comorbidities (e.g., psychiatric illness, diabetes mellitus, hypertension, cardiovascular heart disease, and hypoalbuminemia). 34,37 Although there are knowledge gaps with respect to effective treatment options for depression and anxiety in ESKD, early identification and treatment of emotional symptoms is critical. Pharmacological treatment approaches are frequently used, but nonpharmacological approaches, including pragmatic and evidence-based psychological interventions should also considered.…”
Section: Depression and Anxietymentioning
confidence: 99%
“…5,6 The Living Donor Navigator program (LDN) is one such effort, with one study having found that people who chose to participate in the program were 7 times more likely to receive a living donor kidney transplant. 5 Patients with end-stage kidney disease across sex, race/ethnicity, age, socioeconomic status, and geographic boundaries are disproportionately disadvantaged, low-resourced, and lack adequate transportation compared to the general population 7–10 ; often, additive resources, such as advocacy training programs, perpetuate difficulties in program uptake and sustainability in such a vulnerable population. 11 Thus, innovative strategies designed to bring the living donor kidney transplantation educational programming to the participant, such as telehealth, are warranted.…”
Section: Introductionmentioning
confidence: 99%